HAKIKATPENYATUAN DALAM SAMADHI PADA PATANJALA YOGADARSANA - I Gede Agus Suparta (Jnanasidanta, 2020)
The nature of unity in Samadhi Pada (Patanjala Yogadarsana) is a collection of interactions for a sadhaka who understands spiritual life with the aim of achieving freedom. Practicing yoga is not just training the body and flexibility of the body, helping to train oneself as a form of devotion or devotion that is really sincere, change the caution that leads to the creation of defilements or kle. Yoga teaches one not to cling to results (vairagya), focus on continuous effort, determination and concentration of consciousness. Maintaining awareness of inner recovery is very important to do by convincing it. So as not to be carried away by the illusions of the five senses and the mind which leads one to mistake in perspective. Mistakes in the way of viewing phenomena that are accepted by the mind, can give a wrong perception. Therefore, improving yoga must be very careful in carrying out every process of practice. In other words, it must be complete yoga must always be introspective, aware and conscious in every action both externally and internally.